Analisis Sistem Informasi Manajemen Bencana (Simba)Pada Penanganan Gempa Mamuju Dan Penyebaran Informasi Darurat - Nurjannah; Marsya; Hari Yeni (Jurnal Ilmu Teknologi Informasi Indonesia, 2026)
This study evaluates the effectiveness of the Disaster Management Information System (SIMBA) in handling the Mamuju Earthquake. Using a quantitative descriptive method with 29 respondents, the study measures aspects of system usability, information quality, and coordination impact. The reliability test resulted in a Cronbach’s Alpha value of 0.919, indicating high internal consistency. The findings show that 58.6% of respondents agreed that the system interface is clear, and 53.6% stated that disaster response became faster. However, 13.8% of respondents experienced access constraints due to unstable network conditions. It can be concluded that SIMBA is effective as a coordination tool; however, the development of a low-bandwidth mode is highly necessary to ensure access stability in critical conditions.